Happimetrics leveraging AI to untangle the surprising link between ethics, happiness and business success - Gloor, Peter A. 1961- (Edward Elgar Publishing, 2023)
"Based on 20 years of research, this book lays out a proven and tested method for reaching the goal of employee happiness, analyzing individuals' communication patterns, and making them self-aware by mirroring their behaviour back to them in a privacy-respecting way. In doing so, Peter A. Gloor introduces artificial intelligence-based methods to identify personality, moral values, and ethics of individuals based on their body language and interaction with others."--Amazon.com viewed May 17, 2023
Keywords: Employee morale; Artificial intelligence / Industrial applications